Fragrant Pandan (Pandanus ammaryllifolius) Leaves Ethanol Extract as an Enhancer of Endogenous Antioxidant Defence under High-Fat Diet Conditions - Ni Made Wiasty Sukanty; Laksmi Nur Fajriani; I Putu Bayu Agus Saputra; Iptan Ariki; I Ketut Agus Yura Aditya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Excessive fat consumption, especially saturated and trans fatty acids, plays a significant role in metabolic disorders such as obesity, dyslipidemia, and cardiovascular disease through increased oxidative stress. Malondialdehyde (MDA), the end product of lipid peroxidation, serves as a biomarker of oxidative damage, whereas indirect bilirubin acts as an endogenous antioxidant. This study aimed to evaluate the effect of fragrant pandan leaves ethanol extract (FPLEE) in reducing MDA levels and modulating indirect bilirubin activity in rats fed a high-fat diet (HFD). The experimental method used 24 male Rattus norvegicus divided into six treatment groups: normal control (NC), positive control (C+), negative control (C-), and three FPLEE treatment groups with different doses (8, 16, and 32 mg/200 g BW/day). Administration was carried out for 14 days after 14 days of HFD induction. MDA levels were measured using the ELISA method, while total bilirubin and direct bilirubin were measured using spectrophotometry to determine indirect bilirubin levels. Statistical analysis was performed using one-way ANOVA and the post hoc Bonferroni test. The results showed that there were no significant differences in MDA levels between groups, although the C+ group fed a HFD showed a tendency toward increased MDA. Indirect bilirubin levels increased significantly in the low-dose FPLEE group (8 mg/200 g BW/day), indicating increased endogenous antioxidant activity, while higher doses did not. Thus, FPLEE has the potential to be an effective natural phytopharmaceutical agent in enhancing the body's antioxidant defence against oxidative stress caused by excessive fat consumption, especially at low doses.